2009
DOI: 10.1073/pnas.0811093106
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis ORC1 is a PHD-containing H3K4me3 effector that regulates transcription

Abstract: Control of gene expression depends on a complex and delicate balance of various posttranslational modifications of histones. However, the relevance of specific combinations of histone modifications is not fully defined. Downstream effector proteins recognize particular histone modifications and transduce this information into gene expression patterns. Methylation of histone H3 at lysine 4 (H3K4me) is a landmark of gene expression control in eukaryotes. Its recognition depends on the presence in the effector pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 39 publications
(63 reference statements)
0
27
1
2
Order By: Relevance
“…To investigate the molecular basis underlying the linkage of plant DNA replication to histone mark recognition, we focused on the Arabidopsis ORC1, since it has a fused BAH-PHD cassette at its N-terminus, containing two known structural modules that recognize histone marks (Figure 1A and S1). Although it was reported previously that the isolated Arabidopsis ORC1b PHD finger alone can recognize the H3K4me3 mark by in vitro pulldown assay (de la Paz Sanchez and Gutierrez, 2009), our ITC data revealed that both Arabidopsis ORC1a and ORC1b PHD fingers exhibit a strong preference for unmodified H3 peptide over its methylated H3K4 peptide counterparts (Figure 1B and 1C). …”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…To investigate the molecular basis underlying the linkage of plant DNA replication to histone mark recognition, we focused on the Arabidopsis ORC1, since it has a fused BAH-PHD cassette at its N-terminus, containing two known structural modules that recognize histone marks (Figure 1A and S1). Although it was reported previously that the isolated Arabidopsis ORC1b PHD finger alone can recognize the H3K4me3 mark by in vitro pulldown assay (de la Paz Sanchez and Gutierrez, 2009), our ITC data revealed that both Arabidopsis ORC1a and ORC1b PHD fingers exhibit a strong preference for unmodified H3 peptide over its methylated H3K4 peptide counterparts (Figure 1B and 1C). …”
Section: Resultscontrasting
confidence: 79%
“…Plant ORC1 proteins possess a BAH domain, but unlike yeast and metazoans, there is a PHD finger embedded within the primary sequence of the BAH domain, thereby generating a plant-specific fused BAH-PHD cassette arrangement (Figure 1A and S1). The PHD finger of Arabidopsis ORC1 was reported to bind H3K4me3 peptides by an in vitro pull-down assay (de la Paz Sanchez and Gutierrez, 2009). At the genome level, Arabidopsis DNA replication origin sites exhibit correlation with G+C enriched regions, and histone H2A.Z, H3K4me2, H3K4me3 and H4K5ac marks, as well as anti-correlation with H3K4me1 and H3K9me2 marks (Costas et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The plant homeodomain (PHD) specifically binds methylated histones (H3K4me3) to promote transcription of downstream genes (De La Paz Sanchez and Gutierrez, 2009). Under normal conditions, PTM resides in the outer membrane of the chloroplast.…”
Section: Novel Retrograde Signaling Pathwaysmentioning
confidence: 99%
“…Interestingly, among the newly isolated partners of BdFTL2, BdES43 contains bromo‐adjacent homology (BAH) and plant homeodomain Zn finger (PHD) domains (Figure S6a). The PHD domain is thought to mediate protein−protein interactions, and usually appears in transcriptional regulators involved in chromatin remodeling (Wysocka et al , ; de la Paz Sanchez and Gutierrez, ; López‐González et al , ; Qian et al , ). Alignment and homology analyses showed that BdES43 was highly similar to AtEBS and AtSHL, especially in functionally important amino acid residues of the BAH and PHD domains, recognizing H3K27me3 and H3K4me3, respectively (Figure S6a–c; Qian et al , ).…”
Section: Resultsmentioning
confidence: 99%